Elaboração da modelagem residencial padrão popular para levantamento e custo dos materiais por softwares de integração BIM - Neves, Yasmin dos Santos (Brasil, 2023)
The dissemination of the methodology Build Information Modeling (BIM) in the environment of construction civil, do if present the lifting of the quantitative. The study looks to introduce a form to accomplish of consumption the materials of mode automated through the software from Autodesk, of Revit®. For the elaboration of the study was used as a basis for a project architectural of a residence standard popular belonging to the program “Minha Casa Minha Vida” made by Caixa Econômica Federal (2023). With the modeling was possible to identify the requirement of knowledge wide of the program for the development of parameterization, not only of materials applied but of possible modifications in families of Revit®, when necessary. Realized the comparison of the lifting esteemed by the notebook technical with the popular residential modeling, the values extracted from the software resulted in many disagreements, according to was realizing adaptations in a project. Finally, was verified through a plugin of extension for Revit®, which use the extraction of quantitative for the composition of costs, which gets budgeting automated through the parameterizations included in the elements modeled, according to are modified.